2014
DOI: 10.1002/nml.21116
|View full text |Cite
|
Sign up to set email alerts
|

Which Leadership Constructs Are Important for Predicting Job Satisfaction, Affective Commitment, and Perceived Job Performance in Profit versus Nonprofit Organizations?

Abstract: As an integrative research effort, the present study critically analyzed the relative importance of six leadership constructs- (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 46 publications
4
59
1
1
Order By: Relevance
“…Dwyer et al () showed that volunteers' satisfaction with their work across diverse nonprofit sectors was predicted by transformational leadership. Recently, Rowold et al () corroborated these findings by showing that transformational leadership was strongly correlated with commitment and satisfaction in several nonprofit samples.…”
Section: Theoretical Backgroundmentioning
confidence: 82%
See 1 more Smart Citation
“…Dwyer et al () showed that volunteers' satisfaction with their work across diverse nonprofit sectors was predicted by transformational leadership. Recently, Rowold et al () corroborated these findings by showing that transformational leadership was strongly correlated with commitment and satisfaction in several nonprofit samples.…”
Section: Theoretical Backgroundmentioning
confidence: 82%
“…Past research on the relation between transformational leadership and performance in the volunteer sector is still rare. Rowold, Borgmann, & Bormann, found only small and sometimes near‐zero correlations. In their study, multiple samples from very different fields (e.g., firefighters, church office administrators, orchestra members) were assessed with the same self‐rated performance measure, and the results were pooled across the samples.…”
Section: Theoretical Backgroundmentioning
confidence: 98%
“…More specifically, TFL theory argues that idealized influence and inspirational motivation domains of TFL help motivate people toward a shared collective goal (Northouse, ). Employees who feel valued as important members responsible for achieving the organization's collective goals experience increased feelings of commitment (Emery & Barker, ; Rowold, Borgmann, & Bormann, ), particularly in nonprofit organizations (McMurray, Pirola‐Merlo, Sarros, & Islam, ; Rowold et al, ).
Hypothesis 4: TFL will be positively associated with affective commitment .
Some scholars have theoretically argued that TFL may not be ideal in facilitating inclusion, indicating that transformational leaders may be more concerned with their own greatness, charisma, and future success than with helping other organizational members feel valued and appreciated (Randel et al, ). Likewise, these scholars indicate a concern that transformational leaders may focus on their own visions of the future than incorporating others ideas about the future (Randel et al, ).…”
Section: Literature and Conceptual Modelmentioning
confidence: 99%
“…Other literature also supports the positive link between commitment and subordinate commitment to service quality. Rowold, Borgmann, & Bormann, (2014) found that transformational leadership style has strong significant influence on affective commitment further, (Barnett et al, 2001;Erkutlu, 2006;Emery & Barker, 2007;Liao & Chuang, 2007). Further, Wallace et al, (2013) stated that the leadership can encourage employees towards commitment.…”
mentioning
confidence: 97%